Impact of body mass index on the efficacy and safety of ipragliflozin in Japanese patients with type 2 diabetes mellitus: A subgroup analysis of 3‐month interim results from the Specified Drug Use Results Survey of Ipragliflozin Treatment in Type 2 Diabetic Patients: Long‐term Use study. Issue 5 (25th March 2019) - Tobe, Kazuyuki; Maegawa, Hiroshi; Tabuchi, Hiromi; Nakamura, Ichiro; Uno, Satoshi
Abstract: Aims/Introduction: Specified Drug Use Results Survey of Ipragliflozin Treatment in Type 2 Diabetic Patients: Long‐term Use is an ongoing postmarketing study of ipragliflozin for long‐term use in Japanese patients with type 2 diabetes mellitus. A subgroup analysis of data from the study was carried out to investigate the impact of obesity on the efficacy and safety of ipragliflozin in this population. Materials and Methods: Patients were divided into the following subgroups according to their body mass index (BMI): <22.0, 22.0 to <25.0, 25.0 to <30.0 and ≥30.0 kg/m 2 . Changes in bodyweight and glycemic parameters up to 3 months were evaluated, as well as adverse drug reactions (ADRs) that occurred during ipragliflozin treatment. Results: In the efficacy analysis set (8, 633 patients), glycemic control and bodyweight statistically significantly improved from baseline to 3 months in all BMI subgroups (all P  <   0.05). No strong correlations were identified between changes in bodyweight and changes in hemoglobin A1c, waist circumference or BMI in any of the subgroups. The incidence of adverse drug reactions was 6.29, 8.44, 11.18 and 11.74% in the <22.0, 22.0 to <25.0, 25.0 to <30.0 and ≥30.0 kg/m 2 groups, respectively ( P  =   0.001), in the safety analysis set ( n  = 11, 053 patients). Conclusions: In Japanese patients with type 2 diabetes mellitus, ipragliflozin improved glycemic control and reduced bodyweight, regardless of BMI. Adverse drug reactions were more common in patients with higher BMI than in those with lower BMI. Abstract : We investigated the influence of obesity on the efficacy and safety of ipragliflozin (a sodium–glucose cotransporter 2 inhibitor) in this subgroup analysis of Specified Drug Use Results Survey of Ipragliflozin Treatment in Type 2 Diabetic Patients: Long‐term Use, an ongoing 3‐year postmarketing study in Japan. Changes in glycemic control and bodyweight, as well as safety end‐points up to 3 months of treatment, were evaluated in patient groups subdivided by body mass index. Ipragliflozin was effective in improving glycemic control and reducing bodyweight, regardless of body mass index.